Islamic Views on Politics, Institutions, and Architecture in Jaya Kopah Village - Maya Febriani Chandra; Fitria Amanda; Wetri Andeswita; Ardika Ikhsan; Kiprah Piawi (Penerbit Hellow Pustaka, 2024)
Islam views politics, institutions, and architecture as interconnected with religion. In Islam, it emphasizes that leaders should be based on deliberation (shura) and piety (taqwa) in politics. Religious institutions function in education and social services, such as mosques. Islamic architecture prioritizes the harmony between function, aesthetics, and spirituality, reflecting simplicity, comfort, and sustainability, and manifests the greatness of Allah in its design. This research aims to examine the Islamic perspective in the fields of politics, institutions, and architecture through qualitative descriptive methods with an observational approach. Field observations indicate the application of these values in real practices within society. In the village of Jaya Kopah, leadership is based on shura (deliberation) and taqwa (piety), religious institutions like PHBI play a significant role in ensuring that Islamic holiday celebrations are carried out smoothly and meaningfully for the community, and traditional houses in Jaya Kopah reflect the principles of beauty and simplicity, though not in decorations that represent Islam.